2007
DOI: 10.15517/rbt.v56i3.5726
|View full text |Cite
|
Sign up to set email alerts
|

Influence of roadside pollution on the phylloplane microbial community of Alnus nepalensis (Betulaceae)

Abstract: Abstract:The North Eastern region of India is undergoing industrial development at a faster rate than expected. Roads form the main system of transportation and communication owing to the hilly topography of the region. Automobiles discharge a number of gaseous and trace metal contaminants. Human activities like stone grinding, road construction and sand milling also increase the atmospheric dust and heavy metal contaminant level. These contaminants get settled on leaf surfaces at roadsides and enter in contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
1
12
1
Order By: Relevance
“…Presence of different vehicular exhausting metals was greater in the roadside site in compare to the non-roadside site (Fig 4).The fluctuation of CFU of bacteria and fungi clearly showed a negatively significant correlation with the variation in labels of Pb, Zn, Cd and Cu in polluted site but in non-roadside sampling site elevated count of microbial populations wasfound, which was not significant between those trace metals and samples collected from the sampling site of Rajarhat (S 2 ).Dust deposition on the phylloplane of the three plants left a damaging effect on the microbial community of the phyllosphere shown by the coefficient correlation data analysis - Table 2‖. These findings were supported by Joshi [21]. That study reflected decrease of bacteria and fungi with increase of pollution at roadside site.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Presence of different vehicular exhausting metals was greater in the roadside site in compare to the non-roadside site (Fig 4).The fluctuation of CFU of bacteria and fungi clearly showed a negatively significant correlation with the variation in labels of Pb, Zn, Cd and Cu in polluted site but in non-roadside sampling site elevated count of microbial populations wasfound, which was not significant between those trace metals and samples collected from the sampling site of Rajarhat (S 2 ).Dust deposition on the phylloplane of the three plants left a damaging effect on the microbial community of the phyllosphere shown by the coefficient correlation data analysis - Table 2‖. These findings were supported by Joshi [21]. That study reflected decrease of bacteria and fungi with increase of pollution at roadside site.…”
Section: Resultsmentioning
confidence: 61%
“…Five mature leaves samples were collected from P 1 , P 2 and P 3 at the two sites in sterilised zipper bags and transported for microbial assay in between twenty-four hours to laboratory. Microbial analysis by isolation of micro-fungi and bacteria was done by serial dilution method as described by Joshi [21]. One gram of leaf sample was weighed and taken in a 250-ml conical flask containing 100 ml of sterilised distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have been conducted on the diversity of epiphytic microbes on annuals or perennials with deciduous leaves (De Jager et al 2001, Joshi 2008) and the long-lasting leaves of evergreen trees such as mangoes (De Jager et al 2001). Recently, Jha et al (2010) showed that the mango fruit surface supports a varied climax community.…”
Section: Introductionmentioning
confidence: 99%
“…There is great variability in bacterial communities even within the same species in tree canopies of Tropical Atlantic Forest [10]. Recent investigations emphasize the negative effects of air pollutants on the phyllosphere microbial community [11]. A typical feature of epiphytic bacterial population is the high variability in space and time.…”
mentioning
confidence: 99%